Nationale sportsstereotyper i dansk sportspresse, 1980-2004 - Eriksen, Michael (Forum for Idræt, 2008)
Artiklen undersøger med udgangspunkt i landsdækkende aviser og fokus på fodbold, den danske sportspresses stereotyper af Tyskland, England og Spanien. Michael Eriksen: Nationale sportsstereotyper in Danish sport press 1980-2004 Football is not just about who’s winning and who’s not. It much more important. In this article the various sporting stereotypes used by the danish sporting press to describe the english, spanish and german national footballteams against the danish national footballteam are identified. These national sporting stereotypes are identified by analyzing a wide range of danish newspapers covering the period 1980-2004. The english are, among other things, described as lions, the germans are frequently referred to by using words originating from the second world war, while the spanish are described as bulls. These stereotypes appear in the way they do as a result of many factors. On the one hand, these stereotypes are a result of football-internal events, and on the other hand footballing external reasons.